TRANSFORMATIONAL LEADERSHIP FOR SCHOOL MANAGEMENT IN THE COVID-19 SITUATION OF THE MAE SUAD EDUCATIONAL MANAGEMENT CENTER UNDER THE MAE HONG SON PRIMARY EDUCATION SERVICE AREA OFFICE 2 - Khamphilai, Jutamas; Saengseemok , Suraphong; Yutthawong, Nonthawat (Journal of MCU Nakhondhat, 2024)
The objectives of the research are 1) To study transformational leadership for educational institution administration in the COVID-19 situation and 2) To find guidelines for developing transformational leadership for educational institution administration in the COVID-19 situation. Target groups include: Teachers of educational institutions in the Mae Suad educational administration center under the Mae Hong Son primary educational service area office 2, there were 120 people and 9 people who provided information were experts. Purposive selection was used according to the specified qualifications. The tools were questionnaires and structured interviews. Data were analyzed by finding frequencies, percentages, means, standard deviations and content analysis. The results of the research found that: Transformational leadership for school administration in the COVID-19 situation of educational institution administrators Overall, the practice is at a high level ( = 4.36, S.D. = 0.40). It has the highest practice, followed by consideration of individuality, inspiration. and intellectual stimulation had the lowest compliance, respectively, guidelines for developing transformational leadership for school administration in the COVID-19 situation. of educational institution administrators is that educational institution administrators should support teachers to work together by using communication to give advice. Build morale and stimulate the performance of personnel so that they can perform until they achieve their objectives. There was a joint analysis of measures to prevent COVID disease in order to set policies, visions, goals, and operational guidelines for educational institutions in the same direction. There is decentralization of responsibility by assigning work in accordance with the knowledge, abilities, aptitudes, and differences of individuals equally. An agreement was created to ensure compliance with disease prevention measures to achieve the objectives according to the vision.